INTERNATIONAL CRIMINAL POLICE ORGANISATION STRATEGIES AND THE NATIONAL EFFORT IN THE FIGHT AGAINST CYBERCRIME IN NIGERIA - AUDU MOMOH AMINU; YAHAYA ABDULLAHI ADADU; MUHAMMED BELLO BABAN’UMMA; LUKA RUTH CALEB; MICHAEL MASHAL JEMLAK (International Studies Journal)
Cybercrime has remained a serious challenge in Nigeria. Various efforts of government to fight the menace have failed to yield the desired result. Most academic writings in Nigeria place much emphasis on the causes and effects of cybercrime, while very little has been done on the Strategies to combat it. On this note, this study examines Interpol Strategies and the national efforts in the fight against Cybercrime in Nigeria. The study is mixed in nature which deals with review of previous literatures and documents. Questionnaires were administered on three hundred and seventy-five (375) respondents drawn from the International criminal Police Organisation (ICPO-Interpol) National Central Bureau (NCB) Abuja, Nigeria Police Force (NPF), Economic and Financial Crime Commission (EFCC) and the Department of State Services (DSS).  Interview was conducted on fifteen (15) selected Participants. The study adopted the Space transition theory propounded by Jaishankar (2008) on the assumption that identity flexibility, dissociative anonymity and poor deterrence in Cyberspace motivate Cybercrime.  The study found that some of the Interpol Strategies have positive complement on the national efforts in the fight against cybercrime in Nigeria. It therefore recommends increased investment on training and capacity building of Law enforcement agencies and Cyber security stakeholders in Nigeria as well as synergy and increased utilization of Interpol platforms/tools for winning the war against Cybercrime in Nigeria.